2020
DOI: 10.1002/jocb.484
|View full text |Cite
|
Sign up to set email alerts
|

Creative, Antagonistic, and Angry? Exploring the Roots of Malevolent Creativity with a Real‐World Idea Generation Task

Abstract: Research is currently witnessing more investigations into malevolent creativity-creativity that is used to intentionally harm others. Inspired by previous methods to measure malevolent creativity, in the present study, we introduce a real-world behavioral task designed to capture individuals' capacity for using creativity for the purpose of attaining malevolent goals in response to everyday, provocative situations. In a sample of 105 students, we found malevolent creativity positively correlated with fluency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 50 publications
1
66
0
Order By: Relevance
“…The positive correlation corroborates the notion that both abilities draw on similar, creativity-related cognitive processes that allow for fluent generation of ideas in the context of social problem solving. It may also signal a general proneness for divergent thinking irrespective of task or problem (see Harris & Reiter-Palmon, 2015), which is supported by moderate to large correlations between (nonaffective) verbal creativity and malevolent creativity (Perchtold-Stefan et al, 2020) as well as between verbal creativity and reappraisal inventiveness (Fink et al, 2017;Weber et al, 2014). Another obvious overarching competency may be (i.e., non-affective, not necessarily creative) verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The positive correlation corroborates the notion that both abilities draw on similar, creativity-related cognitive processes that allow for fluent generation of ideas in the context of social problem solving. It may also signal a general proneness for divergent thinking irrespective of task or problem (see Harris & Reiter-Palmon, 2015), which is supported by moderate to large correlations between (nonaffective) verbal creativity and malevolent creativity (Perchtold-Stefan et al, 2020) as well as between verbal creativity and reappraisal inventiveness (Fink et al, 2017;Weber et al, 2014). Another obvious overarching competency may be (i.e., non-affective, not necessarily creative) verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
“…The required sample size was estimated a priori with G*Power (α = .05, 1−β = 0.80). Effect sizes observed in previous relevant research suggested a minimum of 65 participants for a multiple regression approach (based on correlations of .37 to up to .62 between general creative potential and reappraisal inventiveness or malevolent creativity; Fink et al, 2017;Perchtold-Stefan et al, 2020;Rominger et al, 2018). The final sample comprised 73 participants, aged between 18 and 37 years (M = 23.9, SD = 4.3).…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations